Recent Advances in the Use of Probiotics to Improve Meat Quality of Small Ruminants: A Review - Sudeb Saha; Kohtaro Fukuyama; Marina Debnath; Fu Namai; Keita Nishiyama; Haruki Kitazawa (Microorganisms, 2023)
Meat from small ruminants is considered a high quality and delicacy product in many countries. Several benefits have been perceived from probiotics as dietary supplements, such as improved carcass weight, color, tenderness, flavor, muscle fiber structure, water-holding capacity, and healthy fatty acid profile of the meat. Thus, the present review focuses on the effect of probiotics on improving the quality of meat from small ruminants. Though many benefits have been associated with the use of probiotics, the findings of all the considered articles are not always consistent, and the mechanisms behind improving meat quality are not appropriately defined. This variability of findings could be due to the use of different probiotic strains, dosage rates, number of days of experiment, nutrition, breed, age, and health status of the animals. Therefore, future research should emphasize specific strains, optimal dose and days of administration, route, and mechanisms for the specific probiotic strains to host. This review provides a comprehensive overview of the use of probiotics for small ruminants and their impact on meat quality.